The internationalization and performance of SMEs - Lu, Jane W.; Beamish, Paul W. (Strategic Management Journal, 2001)
We discuss and explore the effects of internationalization, an entrepreneurial strategy employed by small and medium‐sized enterprises (SMEs), on firm performance. Using concepts derived from the international business and entrepreneurship literatures, we develop four hypotheses that relate the extent of foreign direct investment (FDI) and exporting activity, and the relative use of alliances, to the corporate performance of internationalizing SMEs. Using a sample of 164 Japanese SMEs to test these hypotheses, we find that the positive impact of internationalization on performance extends primarily from the extent of a firm's FDI activity. We also find evidence consistent with the perspective that firms face a liability of foreignness. When firms first begin FDI activity, profitability declines, but greater levels of FDI are associated with higher performance. Exporting moderates the relationship FDI has with performance, as pursuing a strategy of high exporting concurrent with high FDI is less profitable than one that involves lower levels of exports when FDI levels are high. Finally, we find that alliances with partners with local knowledge can be an effective strategy to overcome the deficiencies SMEs face in resources and capabilities, when they expand into international markets. Copyright © 2001 John Wiley & Sons, Ltd.